Further studies on the alkaloids of Phaeanthus ebracteolatus (Presl) Merrill. preparation of two new quaternary phaeanthine salts - Joson, Lydia Magno 1932-
Two new crystalline quaternary phaeanthine salts were prepared: phaeanthine methochloride, C38H42O6N2(CH3Cl)2. 7H2O, melting at 218-221(degrees) and phaeanthine methobromide, C38H42O6N2(CH3Br)2.4H2O, melting at 238-240(degrees). Phaeanthine was dehydrogenated with mercuric acetate to a resinous product whose ultra violet absorption spectrum was similar to that of phaeantharine chloride. For structural comparative purposes, papaverine methochloride, melting at 212-15(degrees), was prepared.